Death Anxiety and Its Relationship With Social Support and Gratitude in Older Adults - Saba Poordad; Khodamorad Momeni; Jahangir karami (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Death anxiety as an important issue in the elderly's life can negatively affect health and prevent them from having an effective aging period. The present study investigated the relationship between death anxiety, and gratitude and perceived social support in the elderly. We also estimated death anxiety in the elderly according to the level of gratitude and perceived social support. Methods & Materials This was a descriptive correlational study. The statistical population included all bedroom independent elderly of the Kahrizak Charity Hospital in Tehran Province, Iran (N=515),  including 309 women and 206 women. Applying stratified random sampling method, 220 samples were selected. The research tools were Templer' Death Anxiety Scale, Multidimensional Scale of Perceived Social Support, and Gratitude Questionnaire. Inclusion criteria were obtaining a score of ˃22 in the short cognitive status examination, the age of ˃60 years, primary school education, the lack of emotional disturbances like depression, and a minimum one-year residency at the center. The questionnaires were self-reporting and the study participants were informed about the study design by written consent forms. The obtained data were analyzed by SPSS using Pearson's correlation coefficient and multiple regression analysis.   Results The obtained results revealed a negative and significant relationship between gratitude and death anxiety, as well as perceived social support in the studied elderly (P<0.001). Additionally, the regression analysis results indicated that social support and gratitude could predict death anxiety in the elderly (P<0.001). Conclusion Due to the fact that the variables of gratitude and social support are significant predictors of death anxiety, by creating relevant capacities, we can reduce death anxiety in the elderly.